Strategi KPU Kabupaten Pesawaran dalam Mencegah Manipulasi Suara di Tingkat Panitia Ad Hoc pada Pemilu 2019 - Maidani, Hanizar; Hertanto, Hertanto; Maryanah, Tabah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2020)
Prevention of vote manipulation is an important aspect in realizing democratic elections and integrity. In the 2014 General Election, there was a case of vote manipulation in Pesawaran Regency by the ad hoc committee. Reflecting from the 2014 Electional problem, KPU of Pesawaran Regency has required a strategy to prevent this so it would not reoccur in the 2019 Election. This study aims to (1) find out the potential factors causing the vote manipulation at the level of ad hoc committee (2) to determine the strategy of General Election Commission (KPU) of Pesawaran Regency in preventing this. This research is a descriptive qualitative with a type of similar case study. The results of this research (1) among the potential factors causing vote manipulation included: the weak integrity of the ad hoc committee, the in-proportional honorarium received, the accuracy of the official reports and certificates of the results of vote counting, and the recruitment of the ad hoc committee. Even though there was a big chance for vote manipulation in the 2019 Election in Pesawaran, it is not manifested eventually because the strategy carried out by the KPU of Pesawaran Regency was right (2) Among those strategies (a) Corporate strategy, through strengthening the vision and mission, monitoring as internal supervision, cutting the recapitulation at the village level (b) Program strategy was done through technical guidance and socialization of the legislation regulations c) Resource support strategy was carried out through the recruitment of ad hoc committees, the provision of timely honorariums, and the use of arithmetic technology (d) Institutional strategy was done through the division of divisions and coordination with other institutions. From the four strategies above, KPU of Pesawaran Regency has strengthened a strategy to support resources. Pencegahan manipulasi suara merupakan aspek penting dalam mewujudkan pemilu demokratik dan berintegritas. Pada Pemilu 2014 di Pesawaran terjadi kasus manipulasi suara oleh panitia ad hoc. Berkaca pada Pemilu 2014, KPU Kabupaten Pesawaran membutuhkan strategi untuk mencegah hal tersebut agar tidak terulang pada Pemilu 2019. Penelitian ini bertujuan mengetahui faktor penyebab terjadinya potensi manipulasi suara di tingkat panitia ad hoc dan mengetahui strategi KPU Kabupaten Pesawaran dalam mencegah hal tersebut. Tipe penelitian bersifat deskriptif kualitatif dengan jenis similar case studi. Hasil penelitian (1) Faktor penyebab terjadinya potensi manipulasi suara antara lain lemahnya integritas panitia ad hoc, honorarium tidak sebanding dengan beban kerja, akurasi berita acara dan sertifikat hasil penghitungan suara, dan rektrumen panitia ad hoc. Potensi manipulasi suara pada Pemilu 2019 di Pesawaran sebenarnya besar, namun karena strategi yang dilakukan tepat, maka potensi tersebut tidak manifest. (2) Strategi yang digunakan (a) Strategi organisasi, melalui penguatan visi dan misi, monitoring sebagai pengawasan internal, pemotongan jalur rekap penghitungan suara di tingkat kelurahan/desa (b) Strategi program, melalui bimtek, sosialisasi peraturan perundangan c) Strategi pendukung sumber daya, melalui rekrutmen panitia ad hoc, honor tepat waktu, teknologi situng (d) Strategi kelembagaan, melalui pembagian divisi dan koordinasi dengan lembaga lain. Dari keempat strategi ini yang diperkuat adalah strategi pendukung sumber daya.